The impact of microcredit delivery system towards the performance of microenterprises: the case of Amanah Ikhtiar Malaysia (AIM) / Noratikah Taib - Taib, Noratikah (2016)
The objective of this study is to analyze the impact of microcredit delivery system towards the performance of microenterprises by focusing on Amanah Ikhtiar Malaysia (AIM), the largest microcredit institution in Malaysia. Primary data were used in order to collect data from the respondents. By selecting stratified random sampling technique, a set of questionnaires amounted to 330 were distributed to the respondents, which consist of the borrowers of AIM. The multiple regression analysis shows a significant positive relationship between delivery system and performance of microenterprises. All four categories of delivery system which are two under social management program named entrepreneurship development and monitoring and supervision and another two under management of credit products have significant relationship between delivery system and performance of microenterprise. This study reveals the importance of having balance management between both credit product and social development program.